Bi-component anti-corona high-resistance paint as well as preparation method and application thereof
By using two-component anti-corrosion high-resistance paint, combined with nano core-shell structural modifiers, the existing high-resistance paint has solved the problems of low halo voltage and limited corona resistance in high voltage and large-capacity generator sets, and the improvement of high halo voltage and corona resistance performance has been achieved.
Patent Information
- Application Number
- CN202411963108.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
AI Technical Summary
The existing high-resistance paint has low halo voltage and limited corona resistance in high voltage and large capacity generator sets, making it difficult to meet engineering requirements.
Using a two-component anti-corona high resistance paint, component A includes an epoxy resin, a powder and a first organic solvent, component B includes a polyamide resin and a second organic solvent, and material properties are improved by a nano core-shell structure modifier.
The halogen voltage and corona resistance performance of the high-resistance paint are improved, and a high-resistance layer can be formed on the surface of the motor stator wire rod, reducing the probability of corona occurrence.
Smart Images

Figure BDA0005217866790000061 
Figure BDA0005217866790000071 
Figure BDA0005217866790000072
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrical insulation materials, and in particular relates to a two-component anti-corona high-resistance paint and a preparation method and application thereof. Background Art
[0002] After the introduction, digestion, absorption, domestic substitution and re-innovation of existing large-scale generator insulation technology, it has been actually applied to high-voltage and large-capacity generators such as ultra-supercritical steam turbine generators with a rated voltage of 27kV / rated capacity of 1000MW. In the above-mentioned units, anti-corona high-resistance paint is an important supporting material, which can effectively increase the corona initiation voltage of stator bars and windings, reduce the destructive effect of corona on the insulation structure, and ensure the safe service of the unit.
[0003] As the rated voltage and rated capacity of generator sets continue to increase, the corona problem becomes more and more important, and the requirements for high-resistance paint become more and more stringent. Currently, common high-resistance paints have many shortcomings and are difficult to meet engineering requirements, which are mainly manifested in the following three aspects:
[0004] 1) The corona inception voltage is low. Generally, the highest voltage tested after being made into wire rods is about 30kV. The voltage level is relatively low. This performance is measured by the conventional corona inception voltage.
[0005] 2) The corona resistance performance is limited, especially after the unit has been running for a long time, if it cannot be repaired and maintained in time, it will affect the normal power generation, seriously damage the motor insulation, and even burn the equipment and shut down for repairs. This performance can be measured by maintaining the voltage for a long time under high voltage and observing the degree of damage to the insulation structure caused by corona.
[0006] 3) At present, simply increasing the corona inception voltage requires a lot of material selection and matching, which is very difficult in practice, and improving the corona resistance performance is even more difficult. Summary of the invention
[0007] The purpose of the present invention is to provide a two-component anti-corona high-resistance paint with high corona inception voltage and good corona resistance performance, and a preparation method and application thereof.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] The present invention provides a two-component anti-corona high-resistance paint, comprising component A and component B. Taking the total mass of component A as 100%, component A comprises the following ingredients:
[0010] Epoxy resin 20%~25%,
[0011] Powder 45%~60%,
[0012] The first organic solvent is 15% to 35%,
[0013] The powder is composed of silicon carbide, a nano core-shell structure modifier and a filler, the mass ratio of silicon carbide to the nano core-shell structure modifier is 100:(5-30), the mass ratio of silicon carbide to the filler is 100:(0.5-5), the core of the nano core-shell structure modifier is silicon carbide, and the shell of the nano core-shell structure modifier is selected from one or more of silicon oxide, aluminum oxide and titanium oxide;
[0014] Taking the total mass of component B as 100%, component B includes the following components:
[0015] Polyamide resin 40%~55%,
[0016] The second organic solvent is 45% to 60%,
[0017] The component A and the component B are packaged independently.
[0018] Preferably, based on the total mass of component A being 100%, component A comprises the following ingredients:
[0019] Epoxy resin 20%~25%,
[0020] Powder 50%~60%,
[0021] The first organic solvent is 15% to 35%.
[0022] Preferably, the preparation method of the nano core-shell structure modifier comprises: dispersing silicon carbide in solvent I, selectively adding a catalyst to form a first mixed solution, dissolving a precursor in solvent II, selectively adding a chelating agent to form a second mixed solution, and then dropping the second mixed solution into the first mixed solution for reaction, and washing, filtering, drying and calcining after the reaction is completed. The precursor is selected from one or more of tetraethyl silicate, aluminum isopropoxide, and tetrabutyl titanate.
[0023] In some embodiments, when preparing a silicon oxide shell layer, the preparation method specifically includes: dispersing silicon carbide in solvent I, adding a catalyst, wherein the catalyst is ammonia water with a mass concentration of 20% to 30%, and configuring a first mixed solution, dissolving tetraethyl silicate in solvent II, configuring a second mixed solution, and then dripping the second mixed solution into the first mixed solution, reacting at 20 to 30°C, and then performing the steps of suction filtration, washing, drying and calcining after the reaction. The mass ratio of silicon carbide to tetraethyl silicate in the nano core-shell structure modifier is 1: (1.3 to 1.8), and more preferably 1: (1.5 to 1.7).
[0024] Furthermore, when preparing the silicon oxide shell layer, the reaction time is controlled to be 5 to 6 hours.
[0025] Furthermore, the mass ratio of silicon carbide to catalyst (ammonia water) in the nano core-shell structure modifier is 1:(0.1-0.5), and more preferably 1:(0.2-0.35).
[0026] In some embodiments, when preparing an alumina shell layer, the preparation method specifically includes: dispersing silicon carbide in solvent I to form a first mixed solution, dissolving aluminum isopropoxide in solvent II to form a second mixed solution, and then dropping the second mixed solution into the first mixed solution at 80 to 90°C, keeping the temperature at 70 to 85°C for reaction, and then performing the steps of suction filtration, washing, drying and calcining after the reaction. The mass ratio of silicon carbide to aluminum isopropoxide in the nano core-shell structure modifier is 1: (0.1 to 1.5), and more preferably 1: (0.3 to 0.5), for example 1: 0.3, 1: 0.4, 1: 0.5.
[0027] Furthermore, when preparing the aluminum oxide shell layer, the reaction time is controlled to be 5 to 6 hours.
[0028] In some embodiments, when preparing a titanium oxide shell layer, the preparation method specifically includes: dispersing silicon carbide in solvent I, adding a catalyst, the catalyst is hydrochloric acid with a mass concentration of 5% to 12%, and configuring a first mixed solution, dissolving tetrabutyl titanate and a chelating agent in solvent II, configuring a second mixed solution, and then dripping the second mixed solution into the first mixed solution, reacting at 20 to 30°C, and then performing the steps of suction filtration, washing, drying and calcining after the reaction. The mass ratio of silicon carbide to tetrabutyl titanate in the nano core-shell structure modifier is 1: (2 to 4), and more preferably 1: (2.5 to 3). The chelating agent is glacial acetic acid and / or acetylacetone.
[0029] Furthermore, when preparing the titanium oxide shell layer, the reaction time is controlled to be 5 to 6 hours.
[0030] Furthermore, the mass ratio of silicon carbide to catalyst (hydrochloric acid) in the nano core-shell structure modifier is 1: (0.01-0.05).
[0031] Furthermore, the volume ratio of tetrabutyl titanate to the chelating agent in the nano core-shell structure modifier is (30-50):1.
[0032] Preferably, the solvent I is water (such as distilled water) and / or ethanol.
[0033] Further preferably, the mass volume ratio of silicon carbide to solvent I in the nano core-shell structure modifier is 1 g: (2-20) mL.
[0034] Preferably, the solvent II is ethanol and / or isopropanol.
[0035] Further preferably, the mass volume ratio of the precursor to the solvent II in the nano core-shell structure modifier is 1 g:(0.5-100) mL, further preferably 1:(1-20), for example 1:1, 1:1.5, 1:2, 1:5, 1:10, 1:20.
[0036] Preferably, the calcination temperature is 500-700°C.
[0037] More preferably, the calcination time is 1 to 6 hours.
[0038] Preferably, the mass ratio of silicon carbide to the nano core-shell structure modifier in the powder is 100:(5-20), for example, 100:5, 100:8, 100:10, 100:13, 100:15, 100:18, 100:20. Too much or too little nano core-shell structure modifier additive will affect the performance of the two-component anti-corona high resistance paint. Preferably, the high corona inception voltage and corona resistance performance can be improved simultaneously within the above range.
[0039] Preferably, the mesh size of the silicon carbide in the powder is 300-800 meshes.
[0040] In some embodiments, the silicon carbide in the powder is a mixture of a first silicon carbide and a second silicon carbide. The mesh size of the first silicon carbide is 300 to 350 meshes, and the mesh size of the second silicon carbide is 600 to 800 meshes. Furthermore, the mass ratio of the first silicon carbide to the second silicon carbide is 1:(0.5 to 1.5), and more preferably 1:(0.6 to 1.2). By optimizing silicon carbide, the performance of the two-component anti-corona high-resistance paint can be further improved.
[0041] Preferably, the filler is selected from one or more of acetylene black, graphite, quartz powder, zinc oxide, fumed silica, and red iron oxide.
[0042] Preferably, the first organic solvent and the second organic solvent are independently selected from one or more of toluene, butanol and acetone, and the first organic solvent is the same as or different from the second organic solvent.
[0043] Preferably, the epoxy resin is selected from one or more of E-06, E-03, E-12, and E-20.
[0044] Preferably, the polyamide resin is selected from one or more of low molecular weight polyamide resins 600, 650, and 651.
[0045] The second aspect of the present invention also provides a method for preparing the two-component anti-corona high-resistance paint as described above, comprising the following steps:
[0046] (1) mixing an epoxy resin, a portion of a filler and a first organic solvent, then adding silicon carbide, a nano core-shell structure modifier and the remaining portion of the filler, and mixing them evenly to prepare component A;
[0047] (2) The polyamide resin is mixed with the second organic solvent to prepare component B.
[0048] The third aspect of the present invention also provides an application of the two-component anti-corona high-resistance paint as described above, which comprises mixing component A and component B in a mass ratio of (10-15):1, then applying the mixture to the end of the wire rod, and forming an anti-corona layer after curing.
[0049] Preferably, the curing temperature is 20-30°C.
[0050] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0051] The two-component anti-corona high-resistance paint provided by the present invention has high resistance, high corona inception voltage and high voltage resistance, and can form a high-resistance layer on the surface of the motor stator wire rod to reduce the surface electric field strength, thereby reducing the probability of corona occurrence. DETAILED DESCRIPTION
[0052] The present invention is further described below in conjunction with the examples. However, the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to the different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0053] Unless otherwise specified, the raw materials involved in the following examples and comparative examples are all commercially available products, or can be prepared by referring to existing preparation methods.
[0054] Unless otherwise specified, the preparation method of the core-shell structure modifier SiC@SiO2 used below is as follows:
[0055] Preparation method of SiC@SiO2I:
[0056] Take 100mL of distilled water and place it in a three-necked flask, add 15g of the nuclear raw material powder to be processed (silicon carbide), stir and ultrasonically disperse for 0.5h, then add 3mL of 25% ammonia water, stir for 10min to obtain solution A. Take another 25mL of tetraethyl silicate and 40mL of anhydrous ethanol, mix and stir for 10min, put them into a dropping funnel, drip into solution A at a rate of 1 drop / min, continue stirring, and react at room temperature for 6h after the addition is completed. Filter the powder, wash it in 100mL of distilled water, filter it, wash and pump it again as before, dry it at 100℃, calcine it at 600℃ for 4h, and sieve it. Dry it before use (120-130℃, 1-2h) to remove moisture.
[0057] Preparation method of SiC@SiO2II:
[0058] Take 100mL of distilled water and place it in a three-necked flask, add 15g of the nuclear raw material powder to be processed (silicon carbide), stir and ultrasonically disperse for 0.5h, then add 5mL of 25% ammonia water, stir for 10min to obtain solution A. Take 30mL of tetraethyl silicate and 50mL of anhydrous ethanol, mix and stir for 10min, put them into a dropping funnel, drip into solution A at a rate of 1 drop / min, continue stirring, and react at room temperature for 7h after the addition is completed. Filter the powder, wash it in 100mL of distilled water, filter it, wash and pump it again as before, dry it at 100℃, calcine it at 700℃ for 4h, and sieve it. Dry it before use (120-130℃, 1-2h) to remove moisture.
[0059] Preparation method of SiC@SiO2III:
[0060] Take 100mL of distilled water and place it in a three-necked flask, add 15g of the nuclear raw material powder to be processed (silicon carbide), stir and ultrasonically disperse for 0.5h, then add 5mL of 25% ammonia water, stir for 10min to obtain solution A. Take 30mL of tetraethyl silicate and 50mL of anhydrous ethanol, mix and stir for 10min, put them into a dropping funnel, drip into solution A at a rate of 1 drop / min, continue stirring, and react at room temperature for 8h after the addition is completed. Filter the powder, wash it in 100mL of distilled water, filter it, wash and pump it again as before, dry it at 100℃, calcine it at 700℃ for 6h, and sieve it. Dry it before use (120-130℃, 1-2h) to remove moisture.
[0061] Unless otherwise specified, the preparation method of the core-shell structure modifier SiC@Al2O3 used below is as follows:
[0062] Take 100mL of distilled water and 5g of nuclear raw material powder (SiC), place them in a three-necked flask, keep the temperature in a water bath at 85℃, and stir evenly. Take another 2g of aluminum isopropoxide, slowly dissolve it in 30mL of 70℃ isopropanol, and slowly drip it into the three-necked flask through a dropping funnel. After dripping, keep the temperature in a 75℃ water bath for 5h, filter to get the powder, wash it in 100mL of distilled water, filter it, wash and pump it again as before, get the powder, dry it at 100℃, calcine it at 500℃ for 1~2h, and sieve it. Dry it before use (120~130℃, 1~2h) to remove moisture.
[0063] Unless otherwise specified, the preparation method of the core-shell structure modifier SiC@TiO2 used below is as follows:
[0064] Take 40mL of tetrabutyl titanate, 30mL of anhydrous ethanol, 1mL of glacial acetic acid or acetylacetone, mix at room temperature, and place in a dried dropping funnel to obtain solution A. Take another 30mL of anhydrous ethanol, 3.6mL of distilled water, 0.5mL of dilute hydrochloric acid (mass concentration is 10%), and 15g of the nuclear raw material powder to be processed (SiC), place in a three-necked flask and stir evenly. Slowly add solution A to the three-necked flask to obtain a sol, react at room temperature (25±5℃) for 4-8h, filter to obtain a solid, place in 100mL of distilled water for washing, filter, wash again and then pump again to obtain a powder. Dry at 100℃, calcine at 600℃ for 2h, and sieve. Dry before use (120-130℃, 1-2h) to remove moisture.
[0065] If there is no special explanation, the sample test is carried out according to the following method. First, a wire rod is made according to the rated voltage of 27kV, and the wire rod is impregnated and cured by the VPI process. Then, the surface of the wire rod is cleaned, and the anti-corona high-resistance paint of each embodiment and comparative example is applied to the surface of the insulation layer of the wire rod by brushing or spraying (the total length of the wire rod is 1850mm, and the low-resistance paint is applied in the middle 500mm, and the high-resistance paint is applied symmetrically outward at both ends. The length of the overlapping part is 25mm, the total length of the high-resistance paint is 620mm, and the low-resistance paint is JF-130A paint, produced by Suzhou Jufeng Insulation System Co., Ltd.), the thickness of the anti-corona layer is 200-300μm, and electrodes are made at the low-resistance part and the end of the wire rod for testing. The corona inception voltage is tested, and the industrial frequency AC voltage is applied at 80kV and 1min. It is passed if there is no creepage, no longitudinal discharge, no smoke and no ablation on the surface of the anti-corona layer, otherwise it is failed.
[0066] Example 1
[0067] A two-component anti-corona high-resistance paint is prepared according to the following steps:
[0068] Step 1, take 50 grams of toluene solvent and 50 grams of butanol solvent respectively, mix them evenly and use them as a mixed solvent. Take 100 grams of bisphenol A epoxy resin E-20 (Jiangsu Sanmu Group Co., Ltd.) and 0.5 grams of fumed silica, disperse them in a mixed solvent to prepare a resin varnish. Weigh 100 grams of 320 mesh silicon carbide powder and 120 grams of 600 mesh silicon carbide powder, stir evenly, add 15 grams of SiC@SiO2Ⅰ, a core-shell structure modifier with SiO2 as the shell and SiC as the core, and 2 grams of red iron oxide, stir evenly to prepare resin component A.
[0069] Step 2: weigh 25 grams of toluene and 25 grams of butanol to prepare a mixed solvent, weigh 40 grams of low molecular weight polyamide resin 600 (Jiangsu Sanmu Group Co., Ltd.), dissolve it in the mixed solvent, and prepare a curing agent component B.
[0070] Step three, during construction, mix the resin component A and the curing agent component B in a mass ratio of 10:1, apply with a roller, and dry at room temperature to obtain the anti-corona layer.
[0071] Comparative Example 1-1
[0072] It is basically the same as Example 1, except that 15g of the core-shell structure modifier SiC@SiO2I is replaced with 12g of 600-mesh silicon carbide and 3g of silicon dioxide nanopowder. The silicon dioxide nanopowder manufacturer is Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., the brand is XFI03, the particle size is 20nm, and the purity is 99.9%.
[0073] Comparative Example 1-2
[0074] It is basically the same as Example 1, except that the core-shell structure modifier SiC@SiO2I is not added, and the other parts remain unchanged.
[0075] The performance test results are shown in Table 1.
[0076] Table 1
[0077]
[0078] Example 2
[0079] Step 1: Take 50 grams of toluene solvent and 50 grams of butanol solvent respectively, mix them evenly and use them as a mixed solvent. Take 100 grams of bisphenol A epoxy resin E-20 and 0.5 grams of fumed silica, disperse them in a mixed solvent to prepare a resin varnish. Weigh 100 grams of 320 mesh silicon carbide powder and 120 grams of 600 mesh silicon carbide powder, stir evenly, add 24 grams of SiC@Al2O3, a core-shell structure modifier with Al2O3 as the shell and SiC as the core, and 1 gram of acetylene black, stir evenly to prepare resin component A.
[0080] Step 2: weigh 25 grams of toluene and 25 grams of butanol to prepare a mixed solvent, weigh 40 grams of low molecular weight polyamide resin 600, and dissolve it in the mixed solvent to prepare a curing agent component B.
[0081] Step 3: During construction, mix the resin component A and the curing agent component B in a mass ratio of 12:1, apply with a roller, and dry at room temperature to obtain the anti-corona layer.
[0082] Comparative Example 2-1
[0083] It is basically the same as Example 2, except that the core-shell structure modifier SiC@Al2O3 is replaced by 20 grams of 600 mesh silicon carbide and 4 grams of Al2O3 nanopowder. The Al2O3 nanopowder manufacturer is Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., model XFI08, particle size 10-15nm, purity 99.9%.
[0084] Comparative Example 2-2
[0085] It is basically the same as Example 2, except that the core-shell structure modifier SiC@Al2O3 is not added, and the other parts remain unchanged.
[0086] The performance test results are shown in Table 2.
[0087] Table 2
[0088]
[0089] Example 3
[0090] Step 1: Take 50 grams of toluene, 25 grams of butanol and 25 grams of acetone respectively, mix them evenly and use them as a mixed solvent. Take 100 grams of bisphenol A epoxy resin E-20 and 0.5 grams of fumed silica, disperse them in the mixed solvent to prepare a resin varnish. Weigh 100 grams of 320 mesh silicon carbide powder and 80 grams of 800 mesh silicon carbide powder, stir evenly, add 30 grams of SiC@TiO2 core-shell modifier with TiO2 as shell and SiC as core, 2 grams of graphite, and 2 grams of ZnO, stir evenly to prepare resin component A.
[0091] Step 2: weigh 25 grams of toluene and 25 grams of butanol to prepare a mixed solvent, weigh 40 grams of low molecular weight polyamide resin 600, and dissolve it in the mixed solvent to prepare a curing agent component B.
[0092] Step three, during construction, mix the resin component A and the curing agent component B in a mass ratio of 10:1, apply with a roller, and dry at room temperature to obtain the anti-corona layer.
[0093] Comparative Example 3-1
[0094] It is basically the same as Example 3, except that the core-shell structure modifier SiC@TiO2 is replaced by 24 grams of 800 mesh silicon carbide and 6 grams of TiO2 nanopowder. The TiO2 nanopowder manufacturer is Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., model XFI63, particle size 30-50nm, rutile type.
[0095] Comparative Example 3-2
[0096] It is basically the same as Example 3, except that the core-shell structure modifier SiC@TiO2 is not added, and the other parts remain unchanged.
[0097] The performance test results are shown in Table 3.
[0098] Table 3
[0099]
[0100]
[0101] It can be seen from the above table that by adding core-shell structure modifier, the corona inception voltage of anti-corona high resistance paint can be effectively improved and the anti-corona performance can be improved.
[0102] Example 4-1 to Example 4-3, Comparative Example 4
[0103] It is basically the same as Example 1, except that step 1 is different. Step 1 of this embodiment is specifically as follows:
[0104] Take 50g of toluene solvent and 50g of butanol solvent respectively, mix them evenly and use them as mixed solvent. Take 100g of bisphenol A epoxy resin E-20 and 0.5g of fumed silica, disperse them in the mixed solvent to prepare resin varnish. Weigh 100g of 320 mesh silicon carbide powder and xg of 600 mesh silicon carbide powder, stir evenly, add yg of core-shell structure modifier SiC@SiO2Ⅰ with SiO2 as shell and SiC as core, the total of x and y is fixed at 135g, 4g of acetylene black, stir evenly, and prepare resin component A.
[0105] The performance test results are shown in Table 4.
[0106] Table 4
[0107]
[0108] It can be seen from Table 4 that with the increase in the amount of core-shell structure modifier, the corona inception voltage shows a trend of first increasing and then decreasing, indicating that the core-shell structure modifier has a threshold effect and a supersaturation effect.
[0109] Comparative Example 5-1
[0110] It is basically the same as Example 1, except that the core-shell structure modifier is different. In this comparative example, the core-shell structure modifier is SiC@SiO2Ⅱ.
[0111] Comparative Example 5-2
[0112] It is basically the same as Example 1, except that the core-shell structure modifier is different. In this comparative example, the core-shell structure modifier is SiC@SiO2Ⅲ.
[0113] The performance test results are shown in Table 5.
[0114] Table 5
[0115]
[0116]
[0117] Compared with SiC@SiO2I, the amount of tetraethyl silicate used in SiC@SiO2Ⅱ and SiC@SiO2Ⅲ increases, and the reaction conditions become longer, which may lead to an increase in the thickness of the silicon dioxide layer. As a functional regulating component, the shell layer achieves the modification purpose by regulating the electron movement of the core material SiC, and requires an appropriate thickness, not the thicker the better.
[0118] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A two-component anti-corona high-resistance paint, characterized in that: Comprising component A and component B, taking the total mass of component A as 100%, component A comprises the following ingredients: Epoxy resin 20%~25%, Powder 45%~60%, The first organic solvent is 15% to 35%, The powder is composed of silicon carbide, a nano core-shell structure modifier and a filler, the mass ratio of silicon carbide to the nano core-shell structure modifier is 100:(5-30), the mass ratio of silicon carbide to the filler is 100:(0.5-5), the core of the nano core-shell structure modifier is silicon carbide, and the shell of the nano core-shell structure modifier is selected from one or more of silicon oxide, aluminum oxide and titanium oxide; Taking the total mass of component B as 100%, component B includes the following ingredients: Polyamide resin 40%~55%, The second organic solvent is 45% to 60%, The component A and the component B are packaged independently.
2. The two-component anti-corona high-resistance paint according to claim 1, characterized in that: The preparation method of the nano core-shell structure modifier comprises: dispersing silicon carbide in solvent I, selectively adding a catalyst to prepare a first mixed liquid, dissolving a precursor in solvent II, selectively adding a chelating agent to prepare a second mixed liquid, then dropping the second mixed liquid into the first mixed liquid for reaction, and washing, filtering, drying and calcining after the reaction is completed. The precursor is selected from one or more of tetraethyl silicate, aluminum isopropoxide and tetrabutyl titanate.
3. The two-component anti-corona high-resistance paint according to claim 2, characterized in that: When preparing a silicon oxide shell layer, the preparation method specifically includes: dispersing silicon carbide in solvent I, adding a catalyst, wherein the catalyst is ammonia water with a mass concentration of 20% to 30%, to prepare a first mixed solution, dissolving tetraethyl silicate in solvent II to prepare a second mixed solution, and then dropping the second mixed solution into the first mixed solution, reacting at 20 to 30° C., and then performing the steps of suction filtration, washing, drying and calcining after the reaction is completed. The mass ratio of silicon carbide to tetraethyl silicate in the nano core-shell structure modifier is 1:(1.3 to 1.8); When preparing an alumina shell layer, the preparation method specifically comprises: dispersing silicon carbide in solvent I to prepare a first mixed solution, dissolving aluminum isopropoxide in solvent II to prepare a second mixed solution, and then dropping the second mixed solution into the first mixed solution at 80 to 90° C., and reacting at 70 to 85° C., and then filtering, washing, drying and calcining after the reaction is completed. The mass ratio of silicon carbide to aluminum isopropoxide in the nano core-shell structure modifier is 1: (0.1 to 1.5); When preparing a titanium oxide shell layer, the preparation method specifically includes: dispersing silicon carbide in a solvent I, adding a catalyst, wherein the catalyst is hydrochloric acid with a mass concentration of 5% to 12%, to prepare a first mixed solution, dissolving tetrabutyl titanate and a chelating agent in a solvent II, to prepare a second mixed solution, and then dripping the second mixed solution into the first mixed solution, reacting at 20 to 30° C., and after the reaction is completed, performing the steps of suction filtration, washing, drying and calcining. The mass ratio of silicon carbide to tetrabutyl titanate in the nano core-shell structure modifier is 1:(2 to 4), and the chelating agent is glacial acetic acid and / or acetylacetone.
4. The two-component anti-corona high-resistance paint according to claim 2 or 3, characterized in that: The solvent I is water and / or ethanol, and the solvent II is ethanol and / or isopropanol; and / or, The calcination temperature is 500-700° C. and the calcination time is 1-6 hours.
5. The two-component anti-corona high-resistance paint according to claim 1, characterized in that: The mass ratio of silicon carbide to the nano core-shell structure modifier in the powder is 100:(5-20).
6. The two-component anti-corona high-resistance paint according to claim 1, characterized in that: The filler is selected from one or more of acetylene black, graphite, quartz powder, zinc oxide, fumed silica, and red iron oxide.
7. The two-component anti-corona high-resistance paint according to claim 1, characterized in that: The first organic solvent and the second organic solvent are independently selected from one or more of toluene, butanol, and acetone, and the first organic solvent is the same as or different from the second organic solvent.
8. The method for preparing a two-component anti-corona high-resistance paint according to any one of claims 1 to 7, characterized in that: The steps include: (1) mixing an epoxy resin, a portion of a filler and a first organic solvent, then adding silicon carbide, a nano core-shell structure modifier and the remaining portion of the filler, and mixing them evenly to prepare component A; (2) The polyamide resin is mixed with the second organic solvent to prepare component B.
9. Use of the two-component anti-corona high-resistance paint according to any one of claims 1 to 7, characterized in that: The application comprises mixing component A and component B evenly in a mass ratio of (10-15):1, then applying the mixture to the end of a wire rod, and forming an anti-corona layer after curing.